Are E‐cigarettes a safe and good alternative to cigarette smoking?. (31st December 2014) - Rom, Oren; Pecorelli, Alessandra; Valacchi, Giuseppe; Reznick, Abraham Z.
Abstract : Electronic cigarettes (E‐cigarettes) are devices that can vaporize a nicotine solution combined with liquid flavors instead of burning tobacco leaves. Since their emergence in 2004, E‐cigarettes have become widely available, and their use has increased exponentially worldwide. E‐cigarettes are aggressively advertised as a smoking cessation aid; as healthier, cheaper, and more socially acceptable than conventional cigarettes. In recent years, these claims have been evaluated in numerous studies. This review explores the development of the current E‐cigarette and its market, prevalence of awareness, and use. The review also explores the beneficial and adverse effects of E‐cigarettes in various aspects in accordance with recent research. The discussed aspects include smoking cessation or reduction and the health risks, social impact, and environmental consequences of E‐cigarettes.